Enhanced Photocatalytic Performance and Kinetic Improvement of Reusable W-based POM Composite for Produced Water Treatment - Tutuk Djoko Kusworo; Andri Cahyo Kumoro; Adalia Veda; Rafi Mafazan; Meitri Bella Puspa; Dita Aulia Azizah; Dani Puji Utomo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Produced water treatment remains a major challenge due to its complex contaminant composition and the limited efficiency and reusability of conventional photocatalysts. Polyoxometalate (POM)-based materials offer high redox activity and structural tunability. This study presents a novel tungsten-based polyoxometalate (W-based POM) composite with enhanced photocatalytic performance and kinetic superiority for produced water treatment. The objective of this work was to synthesize a reusable W-based POM composite and systematically evaluate its photocatalytic activity, adsorption behavior, kinetics, and stability. The composite was synthesized via a solvothermal method using Na₂WO₄·2H₂O and DMF. Photocatalytic experiments were performed by varying catalyst dosage (0.1–0.5 g), irradiation time (30-180 min), and reusability cycles. The W-based POM composite exhibited a rhombic polyhedral morphology with a well-organized three-dimensional POM framework, reduced crystallite size (14.8 nm), and compressive lattice strain, contributing to improved charge mobility. Optical analysis revealed a red-shift in the absorption edge, reducing the band gap from 2.80 eV to 2.25 eV and enhancing visible-light utilization. Photocatalytic experiments demonstrated high treatment efficiency, achieving 90% NH₃–N and 84% total dissolved solids (TDS) removal under UV irradiation within 180 minutes at an optimal dosage of 0.3 g. Adsorption behavior followed the Dubinin–Radushkevich and Temkin isotherm models, indicating an ion-exchange-dominated mechanism, while kinetic analysis revealed a multi-step process governed by intraparticle diffusion. The composite maintained stable performance over three consecutive cycles without significant activity loss. Overall, the results highlight the strong potential of W-based POM composites as efficient, reusable, and scalable photocatalysts for advanced produced water treatment. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).